Time‐Lapse Imaging and Cell Tracking of Migrating Cells in Slices and Flattened Telencephalic Vesicles. Issue 1 (13th February 2018) - Murcia‐Belmonte, Verónica; Expósito, Giovanna; Herrera, Eloísa
Abstract: Neuronal migration is a vital process needed for subsequent assembly and function of neural circuitry during embryonic development. The vast majority of neural progenitors are generated far from their final destination and need to migrate considerable distances to reach their specific cortical layer. Innovations in cell culture techniques and fluorescence microscopy now facilitate the direct visualization of cell movements during cortical development. Here, a detailed protocol to record and analyze a particular type of early migrating neurons, the Cajal Retzius Cells, during the development of the telencephalic vesicles in mammals is described. This method applied to other reporter mouse lines or to electroporated mouse embryos can be also used to analyze the migration of different types of moving neurons during cortical development. © 2017 by John Wiley & Sons, Inc.